3(y-3)/4=-3y

Simple and best practice solution for 3(y-3)/4=-3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(y-3)/4=-3y equation:


y in (-oo:+oo)

(3*(y-3))/4 = -3*y // + -3*y

(3*(y-3))/4-(-3*y) = 0

(3*(y-3))/4+3*y = 0

(3*(y-3))/4+(3*4*y)/4 = 0

3*(y-3)+3*4*y = 0

15*y-9 = 0

(15*y-9)/4 = 0

(15*y-9)/4 = 0 // * 4

15*y-9 = 0

15*y-9 = 0 // + 9

15*y = 9 // : 15

y = 9/15

y = 3/5

y = 3/5

See similar equations:

| 1/3(x-7)+2=6 | | 4.3t-5.1t-2.3=7.6 | | 2.80=z+.5 | | 610/14+71/7= | | 12+4x-16=-7x+9+5 | | 4-(x+5)=3(x-11) | | 231/4-127/10 | | 15-8n=-4(1+4n)-5 | | 7(3x-5)-6=21x-41 | | 2(2x-11)=3(x-10)+4-7 | | 3x-7-5x=4x-3x+1 | | 23-(x+8)=4x-5 | | x+(3x-2)=14 | | (X+5/2)+(x-1/2)=(x-1/3) | | 9z^2+64=0 | | -5x-3(5-2x)=-3+4x | | 1/3x=21 | | 4x+8-7x=8-3x+6 | | 3y^2+5yz-2z^2= | | -5x/8=-20 | | -5/6=-2/3-3/4x | | -98/-14 | | 6g=5g-7 | | 10/-1 | | 6.5x-3.44=5.2-4.3x | | 18+4(5c-2)= | | 3/4=-2/3-5/6x | | (3x/4)=(6/7) | | 7y-4+2y=6y+11 | | 2.7=16/x | | (a)(.08)+a=145.8 | | -7x+3=-10+2 |

Equations solver categories